Juridical Analysis of the Judge's Reasons for Not Imposing Criminal Liability on a Notary in a Case of Forgery of a Will Deed - Popi Yoniawati; I Gusti Ayu Ketut Rachmi Handayani; Ismunarno Ismunarno (SEAN Institute, 2026)
This study aims to explain the juridical reasons why the Surabaya High Court Decision No. 920/PID/2024/PT.SBY did not impose criminal liability on Notary Dedi Wijaya in a case involving the forgery of a will deed committed by the defendant, King Finder Wong. This research employed a prescriptive normative legal method using statutory and case approaches. The analysis focused on the coherence of legal norms, principles, and their application in the court's decision. The primary legal materials consisted of the Indonesian Criminal Code (KUHP), the Law on the Office of Notary (UU Jabatan Notaris), the Indonesian Code of Criminal Procedure (KUHAP), and relevant court decisions, while the secondary legal materials included legal doctrines concerning authority and criminal liability. The findings indicate that the panel of judges concentrated its examination and ruling on the defendant as the accused party, whereas the notary was considered only within the factual evidentiary context concerning the deed-making process and the circumstances subsequently revealed, without establishing any element of criminal intent on the part of the notary. Procedural irregularities during the verification of identity and supporting documents were deemed more appropriately classified as breaches of professional prudence and disciplinary obligations rather than as fulfillment of the constituent elements of a criminal offense required for criminal punishment. The study recommends strengthening minimum verification standards for high-risk notarial deeds, requiring adequate documentation of clients' identities, postponing the execution of deeds when risk indicators arise, and enhancing professional supervision through continuous guidance and compliance audits. These findings provide guidance on the limits of a notary's criminal liability and offer directions for strengthening professional disciplinary enforcement to better protect users of notarial services.